Capuchinha (tropaeolum majus) bioactive compounds and their functionality in the organism (Research, Society and Development, 2021)
Edible flowers (PANC), are increasingly used in the preparation of meals, as they have beneficial potential for human health. The nasturtium (Tropaeolum majus) is a flower recognized for its antioxidant properties and high content of phenolic compounds. This study aimed to evaluate the profile of bioactive compounds, nutritional in human health, such as carotenoids, phenolic compounds, flavonoids and anthocyanins, in edible flowers of the species (Tropaeolum majus) through the application of descriptive review methodology. Through this descriptive review, we sought to collect data on the effects of bioactive compounds from Capuchin on the human body. The search for published bibliographies took place in the Scielo, Academic Google and World Wide Science databases between the years 2004 to 2020 using the descriptors "Capuchinha", "bioactive compounds", phenolic compounds", "anthocyanins" and "carotenoids", " Tropaeolum majus”, “edible flowers”, in total there were 27 articles in Portuguese and English. After reading and evaluation, 20 articles were selected. greater use in food due to its functional or sensory characteristics.